Academic Supervision Management in Improving Teacher Performance at SDN Pekojan 05 and Kalideres 03 in West Jakartaq - Martha Napitupulu; Waska Warta (Green Publisher Indonesia, 2026)
Academic supervision is a strategic agenda in improving the quality of learning in elementary schools. Teachers, as the spearhead of education, need systematic assistance so that their performance continues to improve. This study aims to describe POAC (Planning, Organizing, Actuating, Controlling)-based academic supervision management carried out by school principals in improving teacher performance at SDN Pekojan 05 and SDN Kalideres 03 in West Jakarta. The research method used a qualitative approach with a case study design, employing observation, interviews, and documentation studies involving school principals, teachers, and school supervisors. The results show that academic supervision planning is not yet fully based on the actual needs of teachers; organization remains relatively simple, with the principal playing a dominant role; implementation tends to be formal and administrative, characterized by one-way communication; and supervision focuses more on administrative compliance than on substantive guidance. Limited time, resources, and instruments were the main constraints; however, there was a commitment from the principals to maintain the continuity of supervision. The research conclusion emphasizes that the application of POAC has the potential to strengthen collaboration, accountability, and the effectiveness of academic supervision when accompanied by participatory planning, a structured supervision team, dialogical implementation, and continuous evaluation. It is hoped that this research will contribute to the development of more adaptive, reflective, and sustainable academic supervision policies and practices to improve teacher performance and the quality of learning in elementary schools.